A five-year audit of lower limb amputations below the knee and rehabilitation outcomes: the Durban experience. Issue 2 (4th May 2019) - Manickum, P; Ramklass, SS; Madiba, TE
Abstract : Introduction: Lower limb amputation (LLA) due to diabetes mellitus (DM) is a growing epidemic worldwide. Objectives: To determine the prevalence of LLAs at Addington Hospital from 2010 to 2014 and to explore the rehabilitation outcomes of amputees. Design and setting: A retrospective chart review of LLAs below the knee was undertaken at Addington Hospital. Subjects: Patients who underwent LLAs were filtered from theatre registers. Methodology: A data collection sheet included demographic profile, diabetic status, level of amputation, limb orientation and rehabilitation outcomes. Outcome measures: Study endpoints were prevalence, compliance and rehabilitation outcomes. Results: From 2010 to 2014, 767 LLAs in 667 patients were identified. Mean age was 59 (13.2) years. M:F ratio was 1:1. Of these, 354 patients (53.1%) had DM. Level of amputation was below-knee 57%, trans-metatarsal 12.4% and toectomy 30.6%. Only 116 patients (17.4%) were referred for physiotherapy, of whom 95 (81.9%) attended. Median frequency of physiotherapy visits was five and four for diabetic and non-diabetic amputees respectively. Mobility after rehabilitation was with a walking frame (49%), crutches (32%), prosthesis and crutches (8%), wheelchair-bound (9%) and independent gait (1%). Conclusion: Over half of amputations were associated with DM. The gender incidence was similar. Referral to physiotherapy and adherence thereto was poor.